What does it take? Tips on research and publishing at the 25th anniversary of the Journal of Corporate Finance - Cumming, Douglas (Journal of Corporate Finance, 2021)
I offer insights into publishing as Managing Editor-in-Chief of the Journal of Corporate Finance as it passes its 25th anniversary. The publishing tips are presented with a view towards guiding future authors. Also, I provide an intermediation perspective to publishing to further guide future authors, explaining the role of the publisher alongside the editors in the review process.